Experimental studies on low speed converging nozzle flow with sudden expansion - Ashfaq, Syed; Khan, Sher Afghan (International Journal of Emerging Technology and Advanced Engineering (IJETAE), 2014)
This paper presents the results of experimental studies conducted to study the base pressure field from a convergent nozzle to ascertain the effect of micro jets, the length to diameter ratio, Mach number and area ratio in a suddenly expanded flow. The Mach numbers of the present study are 0.2, 0.4, 0.6, 0.8 and 0.9, respectively. From the results it is found that the micro jets are effective. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied are 2.56, 3.24, 4.84 and 6.25. The L/D ratio of the sudden expansion duct varies from 10 to 1, and tests were conducted for L/D 10, 8, 6, 5, 4, 3, 2 and 1. To study the quality of flow in the enlarged duct wall pressure was measured and it is found that the flow field remains undisturbed in the presence of micro jets.